Statistical Optimization of Operational Parameters for Enhanced Naphthalene Degradation by Photocatalyst - Aijuan Zhou; Jing Peng; Zhaobo Chen; Jingwen Du; Zechong Guo; Nanqi Ren; Aijie Wang (International Journal of Photoenergy)
The optimization of operational parameters for enhanced naphthalene degradation by TiO2/Fe3O4-SiO2 (TFS) photocatalyst was conducted using statistical experimental design and analysis. Central composite design method of response surface methodology (RSM) was adopted to investigate the optimum value of the selected factors for achieving maximum naphthalene degradation. Experimental results showed that irradiation time, pH, and TFS photocatalyst loading had significant influence on naphthalene degradation and the maximum degradation rate of 97.39% was predicted when the operational parameters were irradiation time 97.1 min, pH 2.1, and catalyst loading 0.962 g/L, respectively. The results were further verified by repeated experiments under optimal conditions. The excellent correlation between predicted and measured values further confirmed the validity and practicability of this statistical optimum strategy.